GENRE ECLECTICISM OF THE RETRO-DETECTIVES BY BOGDAN KOLOMIYCHUK - Землянська, А. В.; Землянський, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the issues of the polygenre nature in B. Kolomiychuk’s works from the «Retroroman» series. It is found out that his novels and stories have the detective intrigue and the stylization of the narration for the corresponding epoch, that allows to identify them as retro-detectives, and they also contain features of a spy novel, a mystical mystery and a noir. They are implemented at the level of the detective intrigue, with the depiction of the atmosphere of Lviv in the beginning of the twentieth century, with the help of the mystical and criminal system of heroes of the art works etc.